Views, Barriers, and Suggestions for Colorectal Cancer Screening Among American Indian Women Older Than 50 Years in the Midwest - Melissa K. Filippi; Aimee S. James; Sarah Brokenleg; Myrietta Talawyma; David G. Perdue; Won S. Choi; K. Allen Greiner; Christine M. Daley (Journal of Primary Care & Community Health, 2013)
Objective . Although colorectal cancer (CRC) mortality rates in the US population have shown a decline, American Indian (AI) CRC mortality rates appear to be increasing. CRC screening rates of AIs remain low when compared with other ethnic groups. The research team explored women’s perceptions toward CRC screening, existing barriers, and suggestions to promote education and screening among AI women in Kansas and Missouri. Methods . Using a community-based participatory research approach, the authors conducted 7 focus groups with AI women older than 50 years (N = 52) to better understand their perceptions of and attitudes toward CRC screening. Results . Women recognized barriers to screening, such as embarrassment, privacy issues, fear, insurance, and cost. They countered perceived barriers through inventive suggestions for education and awareness via social support systems and intergenerational relationships. Discussion . CRC screening interventions for AI must be culturally tailored.